Sugar cane industrial heritage in oriental coast of Málaga. A tourist route opportunity - Martin-Bejar, Sergio; Trujillo-Vilches, Francisco Javier; Bermudo-Gamboa, Carolina; Claver Gil, Juan; Sebastián Pérez, Miguel Ángel; Sevilla-Hurtado, Lorenzo (My University, 2021)
Industrial heritage, as a historical and cultural heritage typology, can be considered a new opportunity to generate tourism interest in a zone. Along the 19th century and at the beginning of the 20th century, the oriental coast of Málaga (Spain) was considered a reference area in the sugar cane cultivation and manufacturing. Nowadays, different sugar cane factories assets remain. These assets can be considered an opportunity to increase visitors and to improve the economy of this area. In this work, six sugar cane factories have been evaluated. Different characteristics has been proposed and a value has been assigned to each one. Finally, a route to visit the sugar cane factories proposed has been designed. The main advantages of this tourism route are that can be done in one day, reinforcing the current touristic offer and attracting new visitors to this area
Keywords: Arqueología industrial; Turismo - Málaga; Caña de azúcar - Industria-Málaga; Sugar cane; Industrial heritage; Tourism; Málaga